WELFARE LEVEL OF SMALL SCALE HAIRTAIL FISH LONGLINE FISHERS AT PALABUHANRATU, SUKABUMI - Juan Febrian Panggabean; Roza Yusfiandayani; Fis Purwangka (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Hairtail fish longline fishers in Palabuhanratu make fishing their primary occupation and source of income for their families. However, fishers face various challenges by unstable incomes due to seasonal fluctuations in catchs, low levels of education, and lack of alternative livelihoods. Therefore, this study aims to describe layur longline fisheries activities to classify and analyze the welfare levels of layur longline fishers using parameters from the National Population and Family Planning Board (BKKBN). The research methods included observation and structured interviews, as well as snowball sampling. Data were analyzed using descriptive analysis, welfare analysis according to BKKBN parameters, and Spearman rank correlation analysis to identify indicators that most influence welfare. The results show that layur longline fisheries in Palabuhanratu utilize 3 GT vessels with the main catch being hairtail fish (Trichirus sp.). Hairtail fish longline fishers in Palabuhanratu are categorized as Pre-Prosperous Families 6%, Prosperous Families I 53%, Prosperous Families II 38%, and Prosperous Families III 3%. There are three indicators that most influence the level of welfare with a moderate to very strong relationship, namely indicators 10, 11, and 9, the very strong relationship is in indicator 10 with a correlation coefficient of 0.804. Key words: BKKBN, Palabuhanratu fishers, layur longline, level of fisher's welfare